HUKUM ZAKAT DAN PAJAK PERORANGAN: Studi Komparatif Perspektif Madzhab Syafi’i dan Madzhab Maliki - Ardiansyah, Wahyu (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2022)
Zakat and taxes cannot be separated dichotomously, both are significant assets in alleviating the economic problems of the people. On the other hand, zakat and tax are opposite in practice which simultaneously there are two categories of expenditure legally that someone who issues and gives zakat must also contribute taxes. This becomes odd when a Muslim who pays tithe due to religious teachings, but also legally pays taxes because he is a state. The research method used in the research is comparative. The approach in this study uses descriptive qualitative analysis to explain aspects of differences and similarities from the perspective of zakat and taxes as well as the legal basis of both. The results of the study indicate that zakat and taxes in the perspective of the Syafi'i and Malik schools of law have similar laws, but there are also some fundamental differences regarding their objects. These are as follows (1) The perspective of the Shafi'i school states that the law of zakat and individual taxes is an obligation that must be issued by a person in religion called zakat, while in the state it is called jizyah (tax) or collection of funds for everyone; (2) The perspective of the Malik school of thought states that the law of zakat and taxes is an individual obligation that must be issued and given through the entitled party (agency) and distributed to the person who is entitled to receive it; (3) The legal basis for zakat and individual tax obligations in the Shafi'i and Malik schools are both based on the arguments of the Qur'anic texts contained in Q.S. an-Nisa: 7; Q.S. at-Taubah: 71; Q.S. adz-Dzariyat: 19; and Q.S. al-Bayyinah: 5; about the obligations of Muslims and the rights of the poor as the basis for individual zakat obligations. Meanwhile, the difference between the two lies in the practical object of zakat and the terms used in taxation in the language and definition of Islamic law. Because historically taxes are known through three terms, namely dharabah, jizyah and kharaj which have a general meaning as collecting funds from the head of state to citizens